The impact of initial public offerings on the external growth strategies of entrepreneurial firms - Tobias Schmidt; Michael Dowling; Christian Lechner (The Journal of Entrepreneurial Finance and Business Ventures, 2006)
The goal of this paper is to examine the impact of Initial Public Offerings (IPO) on the investment strategies of young entrepreneurial firms. Hypotheses are developed from the finance, strategy and top management team literature. These are then tested using multivariate methods in order to study post-IPO investment behavior of a global sample of young Internet firms.
Keywords: 650